Creation of sustainable coastal sediment databases for scientific, environmental, and societal applications - Muhamad Fauzi, Nursuhaila; Mohd Nasir, Nur Azlin Atikah; Hashim, Aimie Rifhan; Kamaruddin, Sharir Aizat (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
Sediment is a naturally occurring material that is fragmented by weathering and erosion, and then conveyed by the forces of wind, water, ice, and gravity acting on the particles. Information regarding the specific properties of coastal silt remains scarce, especially in the northern region of Peninsular Malaysia. The databases provide data on sediment pH, moisture content, particle size, and organic matter. The database would assist governmental and industrial entities in managing coastal region development more effectively. Sampling activities encompassed the acquisition of sediment specimens from coastal areas and agricultural fields. The development of the coastal sediment database is consistent with the Sustainable Development Goals established by the United Nations which include SDG 14: Life below water, SDG 2: Zero hunger, SDG 3: Good health and well-being, and SDG 13: Climate action.